SEMANTIC-PRAGMATIC FEATURES OF DISCOURSE MARKER PUES IN MODERN SPANISH PROSE (based on the C. R. Zafon novel «Angel’s game») - Lomakina , Irina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article deals with the discursive marker pues which has various pragmatic functions in Spanish discourse: it connects the fragments of discourse, explains what links exist between its elements, manages the communication process and the interpretation of discourse by the speaker and recipient, correlate, compare and contrast statements in discourse. The studied unit does not only syntactically unite parts of the text, but explains the semantic and pragmatic connections between its parts, and also expresses the speaker's attitude to what he says. An analysis of the semantic-pragmatic functions of Hispanic discursive marker pues reveals extremely wide range of its interpretations depending on the context in which it is used.A lot of uses of discursive marker pues in all types of texts are due to its pragmatic function of connecting and the ethical modality. For the studied unit are basic its functions in the discourse and they go beyond the classification of parts of speech.Since the pragmatic meanings of discursive marker pues is not explained in dictionaries,  they can only be analyzed in contexts. This discursive marker has not the only function to connect the parts of the discourse but organizes them and also it can concertize them, express different attitudes of the speaker to what he communicates. Thus pues also as an argumentative marker can intensify messages, stimulate explanations or discussions, and, on the contrary, cut off the need for further communication finishing the exchange of thoughts. Mentioned functions of discursive marker pues indicate the need to study its pragmatic colors with the subsequent use of these studies in translation theory and in the teaching of Spanish. Proper use and understanding of the vast number of speech uses of discursive marker pues promotes communicative integration into the Spanish-speaking society. On the other hand, ignorance of the pragmatic colors of this discursive marker, its wrong use may lead to misunderstandings. Undoubtedly, the level of language proficiency can be determined by the ability to use and interpret discursive markers, in particular pues, without it the ability of communicative competence is not complete.__________References:• Kiseleva, , Pajar, D. Diskursivnye slova russkogo jazyka: opyt kontekstno-semanticheskogo opisanija [Discursive words of the Russian language: the experience of a contextual description] (Moskva, Metatekst, 1998), 447 (In Russian).• Lomakіna, І. A. «Semantiko-pragmatichnі osoblivostі diskursivnih markerіv u suchasnіj іspans'kіj movі [Semantic-pragmatic features of discourse markers in modern spanish language].» Problemi semantiki, pragmatiki ta kognіtivnoї lіngvіstiki [Problems of semantics, pragmatists and cognitive linguists] 32 (2017): 79-89. (In Ukrainian).• Briz, A., Pons, S. y J. Portolés. Diccionario de partículas discursivas del español (2008), dpde.es.• Fraser, «Towards a Theory of Discourse Markers.» Approaches to Discourse Particles, еd. by K.Fischer (Amsterdam: Elsevier, 2006): 189–204.• Montolío, E. La conexión el el texto académico. Los conectores. Manual pragmático de escritura académica (Barcelona: Ariel, 2002): 105-164.• Portolés,  Marcadores del discurso (Barcelona: Ariel Practicum, 2001).• Schiffrin,  Discourse Markers (Cambridge : Cambridge University Press, 1988), 364.• Zafón, С. El juego del ángel (Planeta, Madrid, 2008), https://epdf.tips/el-juego-del-angel44e2a95b7f0e00b147d9f808702b09ad12335.html
Keywords: discursive marker pues, discourse, semantics, pragmatic functions, Spanish language, communication, translation